Child's Style Influence on Parents Buying Decision Process at Nata De Coco Beverages Product in Bandung City - Darmawan, Iden; Chaerudin, Rendra (Journal of Innovation, Business and Entrepreneurship, 2017)
Abstract. The coconut industry which utilized as nata de coco's business opportunity becomes one of the buffer of economic growth in Indonesia especially in Bandung. To further support so the benefits of nata de coco products can be perceived by every connoisseur needed a marketing process as a tool for the dealer between producers and consumers. This refers to children as the biggest target market for the nata de coco drink business. This study aims to determine the style of children who can influence the purchase decision of parents to drink nata de coco in Bandung. To achieve this goal secondary data is collected through rigorous literature studies ranging from marketing, child style as an influence, parental purchasing decisions until factors that can influence parental purchasing decisions. Followed by primary data collection through consumer survey is distributed through sampling method in Bandung. This study provides new empirical evidence of child style as an influence consisting of (peading style, persistent style, forceful style, demonstrative style, sugar-coated style, threatening style, and pitty style) influencing parents purchasing decision in Bandung City. Data are collected through online and offline questionnaires and distributed through simple linear methods. Total of 100 questionnaires have been collected and used for the analysis of this research. Analyze simple linear regression which applied to determine the interrelations of different variables in parental purchasing decisions. Empirical results indicate that there is a significant relationship between independent variables (child style as an influence) to the dependent variable (parental purchasing decisions). This research is important for marketers in understanding the effect of child's style on parental purchasing decisions.Â Keywords: child style, parental purchasing decisions, nata de coco, marketers, producers, consumers, Bandung.